2021
DOI: 10.4103/jfmpc.jfmpc_1027_20
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of factors for interruption of antitubercular treatment among defaulters in urban and rural areas of Kamrup District, Assam

Abstract: Background: Defaulting from treatment is an important challenge for tuberculosis (TB) control. As per the Revised National Tuberculosis Control Programme quarterly reports of Kamrup District (Assam), among the registered cases default rate was 13.3%(2008) & 13.1 % (2009). Objectives: To elicit reasons & factors responsible for interruption of treatment from a cohort of TB defaulters of urban & rural areas in Kamrup District. Methods: The cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Across 15 studies surveying people who experienced loss to follow-up or medication nonadherence during treatment, clinical reasons included medication side effects (reported by 7% [1/14] [ 112 ] to 47% [15/32] [ 92 ] of people across 15 studies [ 87 , 92 , 102 , 106 , 112 122 ]), long treatment duration (reported by 11% [8/70] [ 121 ] to 16% [5/32] [ 92 ] of people in 2 studies), early symptom improvement (reported by 4% [1/28] [ 119 ] to 55% [110/201] [ 114 ] across 11 studies [ 87 , 92 , 106 , 113 – 117 , 119 121 ]), and lack of symptom improvement (reported by 1% [1/150] [ 117 ] to 34% [11/32] [ 92 ] across 8 studies [ 92 , 113 – 115 , 117 , 120 122 ]) (Fig L in the S6 Appendix ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Across 15 studies surveying people who experienced loss to follow-up or medication nonadherence during treatment, clinical reasons included medication side effects (reported by 7% [1/14] [ 112 ] to 47% [15/32] [ 92 ] of people across 15 studies [ 87 , 92 , 102 , 106 , 112 122 ]), long treatment duration (reported by 11% [8/70] [ 121 ] to 16% [5/32] [ 92 ] of people in 2 studies), early symptom improvement (reported by 4% [1/28] [ 119 ] to 55% [110/201] [ 114 ] across 11 studies [ 87 , 92 , 106 , 113 – 117 , 119 121 ]), and lack of symptom improvement (reported by 1% [1/150] [ 117 ] to 34% [11/32] [ 92 ] across 8 studies [ 92 , 113 – 115 , 117 , 120 122 ]) (Fig L in the S6 Appendix ).…”
Section: Resultsmentioning
confidence: 99%
“…Across 15 studies surveying people who experienced loss to follow-up or medication nonadherence, reported reasons included: work constraints (reported by 1% [1/82] [ 106 ] to 38% [12/32] [ 92 ] of people across 8 studies [ 92 , 106 , 113 – 115 , 118 120 ]); migration or travel (reported by 1% [2/201] [ 114 ] to 91% [20/22] [ 103 ] of people across 9 studies [ 87 , 103 , 106 , 113 , 114 , 116 , 118 , 120 , 121 ]); lack of knowledge of treatment duration or of the risks of treatment interruption (reported by 7% [5/70] [ 121 ] to 25% [14/55] [ 122 ] of people in 4 studies [ 114 , 115 , 121 , 122 ]); TB stigma (reported by 3% [4/141] [ 113 ] to 81% [26/32] [ 92 ] of people across 3 studies [ 87 , 92 , 113 ]); alcohol use (reported by 3% [5/150] [ 117 ] to 35% [29/82] [ 106 ] of people across 5 studies [ 92 , 106 , 113 , 114 , 117 ]); forgetfulness in dose-taking (reported by 19% [15/78] [ 118 ] to 43% [6/14] [ 112 ] of people across 4 studies [ 87 , 112 , 118 , 122 ]); and depression (reported by 7% [27/377] [ 112 ] to 23% [39/167] [ …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation